(untitled) (Proceedings of International Conference on Educational Discoveries and Humanities, 2023)
This in the article fishes between occurring protein exchange in disorders in fish show to be clinical characters appetite loss , coxixia development growth and from development medium stay and your blood biochemical indicators protein exchange in disorders changes about data given .